1996
DOI: 10.1021/jo951842x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Conformational Dynamics of Bridgehead-Substituted Nitrosamines. Di-1-adamantylnitrosamine and Di-1-norbornylnitrosamine

Abstract: The synthesis of two bridgehead-substituted nitrosamines, di-1-adamantylnitrosamine (1) and di-1-norbornylnitrosamine (2), is described, and their solid state crystal structures are reported. Large bridgehead substituents increase the NNO angle of the nitrosamine (compared to that found for dimethylnitrosamine) without deconjugating the NNO pi system significantly. This structural change correlates with a red-shifted optical absorption, a diminished N,N rotational barrier, and a greater ease of oxidation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…The molecular structures of N-nitrosamines exert a pronounced influence on the bioactivity of this class of compounds [11,[16][17][18][19]. For instance, within a set of 235 different nitrosamines tested for carcinogenic activity by Preussmann and Stewart [11], only a few were noncarcinogenic, and the presence of an N-t-butyl group is the common feature of this subset.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular structures of N-nitrosamines exert a pronounced influence on the bioactivity of this class of compounds [11,[16][17][18][19]. For instance, within a set of 235 different nitrosamines tested for carcinogenic activity by Preussmann and Stewart [11], only a few were noncarcinogenic, and the presence of an N-t-butyl group is the common feature of this subset.…”
Section: Introductionmentioning
confidence: 99%
“…Sarker et al [19] have prepared sterically hindered bridgehead-substituted N-alkyl nitrosamines, such that the NNO angle of the nitrosamine is increased (as compared to that of N-Nitrosodimethylnitrosamine) but with no significant deconjugation of the NNO p system. It has been observed that this structural change is accompanied by and correlates with a red-shift in the optical absorption spectrum, a decrease in the N-N rotational barrier, and an increase in the oxidation potential of these hindered nitrosamines, as compared with that of N-Nitrosodimethylnitrosamine [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the various reaction capabilities of their functional group, nitrosamines became valued intermediates in syntheses of numerous organic compounds, and thus, their chemical, biochemical, photochemical, and physical properties are subject of continuing research efforts. Some of the most important advances in nitrosamines structural chemistry were achieved by workers using the methods of 1 H, 13 C, and 15 N NMR spectroscopy. The restricted rotation about the N─N bond in nitrosamines was documented and rationalized by the interaction between the electron lone pair of the amino nitrogen and the π electrons of the ─N═O group (n N ―π NO * conjugation) that confers a partial double‐bond character to these N─N bonds and a preference for a planar geometry (or very nearly so) to the amino nitrogens .…”
Section: Introductionmentioning
confidence: 99%
“…The energy barriers to the restricted N─N rotation have been determined for a considerable number of nitrosamines, and values ranging from 51 up to 100 kJ mol −1 were reported. It has been noted that nitrosamines with the bulkiest alkyl substituents at the amino nitrogen atom show the lowest energy rotational barriers (within 51–84 kJ mol −1 ), whereas those bearing small substituents typically exhibit the highest rotational barriers (95–100 kJ mol −1 This kind of behavior has been rationalized as follows: In nitrosamines with bulky substituents (large, or highly branched in α‐positions), because of the strong steric interaction between the space demanding >N─N═O system and the bulky alkyl substituents at the amino nitrogen, either the ─N═O group, or the N ‐alkyl group, or both of them will undergo deviation from coplanarity, accompanied, among others, by weakened n N ―π NO * conjugation and diminished N─N rotational barrier. In the typical nitrosamines containing small substituents, however, in the absence of any steric strain, the coplanarity of the (C‐α) 2 N─N═O system, the n N ―π NO * conjugation, and together with them, the high N─N rotational barriers are preserved.…”
Section: Introductionmentioning
confidence: 99%